The role of melatonin in the regulation of physiological processes in the eye under normal and pathological conditions and prospects of its application - N. B. Chesnokova; O. V. Beznos (Российский офтальмологический журнал, 2018)
The paper gives an overview of recent data concerning the role of pituitary hormone melatonin in the regulation of different physiological processes in the eye under normal and pathological conditions. Melatonin is a key regulator of circadian rhythm in most known species. In addition, it regulates the expression of numerous genes, is a potent antioxidant, has antiinflammatory, antiangiogenic, immunomodulating, anticancer activity and can decrease intraocular pressure. These and other effects of this hormone offer ample opportunities for the use of melatonin in the therapy of eye diseases // Russian Ophthalmological Journal, 2016; 4: 106-11. doi: 10.21516/2072-0076-2016-9-4-106-111.